1990
DOI: 10.1002/app.1990.070390416
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure, melting behavior, and crystallinity of 1‐octene‐based very low density polyethylenes (VLDPEs) as studied by fractionation and heat capacity measurements with DSC

Abstract: SynopsisHeat capacity measurements with DSC on 1-octene-based very low density polyethylenes (VLDPEs), with densities from 888 to 907 kg/m3, show crystallization between 120 and -60°C and melting between -60 and 130°C. Under the assumption that hardly any octene groups are present in the crystal lattice, the experimental heat capacity values were compared with reference values for purely amorphous and purely crystalline linear polyethylene on the basis of a two-phase model. The enthalpy-based weight crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…Some researchers assigned the additional reflection to the hexagonal mesomorphic phase which is not stable at room temperature and could probably be stabilized by the form of hexyl branches [26,27] and some others have assigned it to a monoclinic crystallization phase reflection [28]. As an overview, it is caused by bulky aliphatic branches which cannot be incorporated in an orthorhombic PE crystal and consequently form some other kinds of "crystal" with an order nature intermediate between crystalline and amorphous [19,29].…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers assigned the additional reflection to the hexagonal mesomorphic phase which is not stable at room temperature and could probably be stabilized by the form of hexyl branches [26,27] and some others have assigned it to a monoclinic crystallization phase reflection [28]. As an overview, it is caused by bulky aliphatic branches which cannot be incorporated in an orthorhombic PE crystal and consequently form some other kinds of "crystal" with an order nature intermediate between crystalline and amorphous [19,29].…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous copolymers have a far more complex molecular structure [1,8,9,32,111]; LLDPE and VLDPE, for example, are blends [1,9,32,47,[111][112][113] of molecules which differ greatly in comonomer content, even at the same chain length. VLDPE molecules show exceptional behaviour: they crystallize and melt across a temperature range of about 200~ above the glass transition [1,35,72]. Therefore, in VLDPE we expect to find all types of crystallites: lamellae with folded ethylene sequences, fringed micelles with bundled ethylene sequences and clusters with loosely packed ethylene sequences.…”
Section: Discussionmentioning
confidence: 98%
“…The VLDPE is an intermolecularly heterogeneous copolymer [35], for it has been found that the copolymer with 8,5 mol % octene in Fig. 2 can be separated into molecules with greatly varying comonomer contents.…”
Section: Homogeneity and Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5]13 Here, we need to point out the shapes of the cooling curves which reveal a distinct heterogeneous transition behavior. Mathot et al [1][2][3] discussed the shape of the DSC curves in terms of intermolecular and intramolecular homogeneity of the distribution of the shortchain branches (SCB) but refer mainly to the heating scans, not the cooling scans.…”
Section: General Description Of Crystallization Andmentioning
confidence: 99%